OECD guidelines on corporate governance of state-owned enterprises. - OECD (Paris OECD, 2015)
The new OECD Guidelines on Corporate Governance of State-Owned Enterprises provide an internationally agreed benchmark to help governments assess and improve the way they exercise ownership functions in state-owned enterprises (SOEs).
Keywords: Government business enterprises--OECD countries